Cloud performance efficiency in Africa - Babasanmi, Opeoluwa Victor (Department of Computer Science, 2023)
Internet and Public Cloud adoption has been growing all over the world. An increasing amount of research has been conducted on Internet Performance across different continents. Major Cloud Providers have a growing presence in Africa, but little study has been conducted on Cloud Performance in Africa. This study undertakes to determine network performance from Africa to Public Cloud providers and compare this with what is achievable in a more developed continent like Europe. To achieve this, RIPE Atlas platform is used to run latency and traceroute measurements from RIPE Atlas endpoints in Africa and Europe to Public Cloud CDN endpoints and Virtual servers in Datacenters publicly available in both continents. Reverse measurements are also conducted from the Virtual servers to non-RIPE endpoints in both Africa and Europe. We find that countries with high network latencies in Africa are using CDN endpoints outside of Africa and, in some cases, make use of circuitous routes to Cloud destinations in Africa. In Europe, we found this to be different, as majority of CDN endpoints used were local to the continent, thereby leading to better CDN performance. While we see that using less expensive CDN PoPs in Africa could provide up to 87 percent performance improvement over relying on the Cloud Regions, Europe achieved up to 142 percent improvement. Following the results of this study, we recommend that Cloud providers should continue to increase their CDN presence in Africa and work with local ISPs to improve routing to ensure that local Cloud infrastructure is optimized for network traffic within the continent.